The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.arth.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

No Threshold Exists for Recommending Revision Surgery in Metal-on-Metal Hip Arthroplasty Patients With Adverse Reactions to Metal Debris: A Retrospective Cohort Study of 346 Revisions

Abstract: Background Surgeons currently have difficulty when managing metal-on-metal hip arthroplasty (MoMHA) patients with adverse reactions to metal debris (ARMD). This stems from a lack of evidence, which is emphasized by the variability in the recommendations proposed by different worldwide regulatory authorities for considering MoMHA revision surgery. We investigated predictors of poor outcomes following MoMHA revision surgery performed for ARMD to help inform the revision threshold and type of reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
2
8
1
Order By: Relevance
“…Of course, pseudotumors are not the only type of lesions related to ARMD and muscle deficiency and osteolysis need to be considered. A CoC bearing surface is reported to be associated with risk for poor outcome in 2 recent British studies (Matharu et al 2017b(Matharu et al , 2019, but neither our study nor an Australian registry-based study (Wong et al 2015) found a difference between different bearing surfaces used for MoM revisions. Ceramic heads are used at our institution to minimize metal release from the trunniontaper junction, and nowadays our bearing surface of choice is CoP, as use of CoC is associated with occasional squeaking (McDonnell et al 2013, Salo et al 2017.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Of course, pseudotumors are not the only type of lesions related to ARMD and muscle deficiency and osteolysis need to be considered. A CoC bearing surface is reported to be associated with risk for poor outcome in 2 recent British studies (Matharu et al 2017b(Matharu et al , 2019, but neither our study nor an Australian registry-based study (Wong et al 2015) found a difference between different bearing surfaces used for MoM revisions. Ceramic heads are used at our institution to minimize metal release from the trunniontaper junction, and nowadays our bearing surface of choice is CoP, as use of CoC is associated with occasional squeaking (McDonnell et al 2013, Salo et al 2017.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study, the association was non-linear, and only Co 20-90 µg/L was associated with an increased risk for re-revision. A few recent studies observed no association with preoperative metal ion levels and poor outcome (Liow et al 2016, Matharu et al 2019. The possible association between whole-blood metal ion concentrations and revision results is clearly complex, needs further investigation and no single metal ion value can be given as a threshold for revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive details of this cohort including the definitions for ARMD, preoperative investigations, intraoperative findings at revision, follow-up after revision surgery, and the outcomes following revision have been described (Matharu et al. 2019). Briefly, both centres were tertiary units with 16 surgeons performing all cases.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately half of patients experiencing metal-on-metal total hip replacement (MoM-THR) subsequently received leading implant-related complications with more than 1/3 undertaking secondary revision surgery [ 1 , 2 ]. Implant-related complications associated with adverse reactions to metal debris (ARMD) have been an increasing concern [ 3 , 4 ]. The occurrence of these complications stimulated by ARMD which is forcefully implicated in the pathophysiology of MoM-THR failure is common and may be associated with osteolysis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%